2011
DOI: 10.17221/2395-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The effect of depuration on heavy metals, petroleum hydrocarbons, and microbial contamination levels in Paphia undulata (Bivalvia: Veneridae)

Abstract: ABSTRACT:The depuration of 8 heavy metals (Zn, Pb, Ni, Mn, Cu, Cr, Co and Cd), total petroleum hydrocarbons and pathogenic bacteria of Paphia undulata was tested and the survival of depurated clams was evaluated. Investigated samples were collected from Ismailia, Egypt. The initial metal concentrations were significantly higher in the whole soft tissues than in water and sediment except for Mn. After 24 h depuration, Zn, Pb, Ni, Mn, Cu, Cr and Cd were significantly reduced to 44, 23, 25, 17, 61, 41, and 75%, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
2
9
1
1
Order By: Relevance
“…But these trials needed long periods for depuration that ranged from 50 days to 6 months. Other studies under took depuration in different experimental conditions (EL-Shenawy, 2004;Saed et al, 2004;El-Gamal, 2011). They found that it needs 2-32 days for complete depuration.…”
Section: Discussionmentioning
confidence: 99%
“…But these trials needed long periods for depuration that ranged from 50 days to 6 months. Other studies under took depuration in different experimental conditions (EL-Shenawy, 2004;Saed et al, 2004;El-Gamal, 2011). They found that it needs 2-32 days for complete depuration.…”
Section: Discussionmentioning
confidence: 99%
“…El-Gamal [67] noticed that Zn, Pb, Ni, Mn, Cu, Cr and Cd can be reduced by 44%, 23%, 25%, 17%, 61%, 41% and 75% in clam, Paphia undulata after immersion in clean artificial seawater for 24 hours, respectively. The same author also showed that depuration process reduced the presence of Vibrio sp.…”
Section: Reducing Health Risk Of Heavy Metal In Bivalvesmentioning
confidence: 99%
“…Many authors have reported depuration times for E. coli in various bivalve species. El-Gamal (2011) stated that E. coli can be completely excreted by Paphia undulata after 72 h of depuration, even if the initial amount is above the threshold level of category B. Barile et al (2009) reported that Chamelea gallina , which was contaminated with 4.0 Log 10 cfu/g E. coli , can reach the marketable level after 48 h depuration.…”
Section: Resultsmentioning
confidence: 99%
“…In several studies it has been stated that a three day depuration process could be enough for excretion of Salmonella ( Barile et al , 2009 ; El-Gamal, 2011 ). El-Shenawy (2004) has reported that clams containing Salmonella in the limits of category B, can be depurated by 90% of initial loads after 4 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation